Typification of the Linnaean name Corispermum squarrosum, with notes on C. hyssopifolium and nomenclatural implications for Agriophyllum (Chenopodiaceae: Corispermeae) - Mosyakin, Sergei L.; Spencer, Mark A. (Phytotaxa, 2017)
The Linnaean name Corispermum squarrosum (Chenopodiaceae, Corispermeae) is lectotypified here by the specimen LINN 12.3. This specimen is identifiable with the plant currently known as C. uralense, a species occurring in southeasternmost regions of Europe and adjacent parts of Siberia and Kazakhstan, and the name C. squarrosum should be now applied to it. Our lectotypification of C. squarrosum restores the original taxonomic application by Linnaeus to an East European species of Corispermum. It is demonstrated that the epithet “squarrosum” was misapplied to several species of Corispermum and one species of Agriophyllum. This long-standing nomenclatural confusion was initiated by Pallas, who, contrary to Linnaeus, considered a species of Agriophyllum as “the only true C. squarrosum”. That concept was then accepted by Moquin-Tandon and Aellen and followed by some other authors. Nomenclatural implications of the lectotypification of C. squarrosum are explained. As a result of our lectotypification, the most widespread species of Agriophyllum (widely known as A. arenarium and “A. squarrosum” sensu Moquin-Tandon), should be called A. pungens. The generic name Agriophyllum was not validly published by Marschall von Bieberstein in 1819 (provisional name), but it was validated by C.A. Meyer in 1831. Relevant updated nomenclatural citations are provided.